DAYA TAHAN SEDIAAN PERMANEN LARVA Culex pipiens DENGAN PERLAKUAN DEHIDRASI MENGGUNAKAN KONSENTRASI ALKOHOL YANG BERBEDA - Intan Kurniawati; Didik Sumanto; Fuad Alhamidy (JURNAL LITBANG, 2007)
Produced the permanent preparation can not leave dehydration process to make null concentration of water on the tissue to defense of morphologlt of tissue preparation on the long times. The good technic of dehydration will give strength the permanent preparation on the long time from autolysis of the cell on the tissue.The goal of this research is to know strengthly of the permonent preparation o.f Culex pipiens larvae with dehydration treatment used diffbrent concentration of alcohol. Dehydration treatntent aplicated to Culex pipiens larvaeas sample, then be produced to permanent preparation and observed it a month (31 days) after treatntent ofdehydration.Dehydration treatment with alcohol 30 % can defense the permanent preparation only for 6 days. But , alcohol 70 % and 96 o% can defense the permanent preparation for 3l days. It means, alcohol 70 % and 96 % is the better concentration of alcohol to produced permanent preparation from the tissue o/larvae of mosquite.Key words : strengthly, pemanent preparation, dehydration